Analisis Pertimbangan Hakim dalam Putusan No.0253/Pdt.P/2016/Pa.Pbg Tentang Dispensasi Pernikahan - Mutakin, Ali; Marwati, Lusi (Tasyri' : Journal of Islamic Law, 2022)
Marriage dispensation is the granting of the right by the Religious Courts to a person to marry even though they have not reached the minimum age for marriage, if the situation "requires" and there is no other option. In an effort to grant a marriage dispensation, the Religious Courts are required to provide considerations that prioritize the concept of maslahah, namely considerations of goodness and rejecting harm (madharat) in society. This article aims to analyze the decision no.0253/Pdt.P/2016/PA.Pbg regarding marriage dispensation. The type of research used is a normative legal research model (doctrinal). The primary data source used is a copy of the decision of the religious court no. 0253/Pdt.P/2016/PA.Pbg, while the secondary data are books, journal articles related to the discussion theme. The data analysis technique used descriptive analysis, where the data obtained were described and then analyzed. The findings of this article are some of the considerations that become the judge's reference in determining decision no. 0253/Pdt.P/2016/PA.Pbg are 1) based on Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage. 2) based on written evidence and statements from the two witnesses. 3) based on the true benefit.